Insight into the adsorption of dyes onto chitin in aqueous solution: An experimental and computational study - Kiki Adi Kurnia; Ardiani Putri Rahayu; Afifah Faradilla Islami; Yuly Kusumawati; I Gede Wenten; Anisa Ur Rahmah; Saepurahman; Diana Vanda Wellia; Asep Saefumillah (Arabian Journal of Chemistry, 2022)
This study aimed to get an insight into the adsorption of three synthetic dyes onto chitin using experimental and computational approaches. The successful preparation of α-chitin was confirmed using the Fourier Transform Infrared (FTIR) and X-ray Diffraction (XRD). In addition, the presence of porous and fiber on the surface of the extracted chitin was revealed by the Scanning Electron Microscopy (SEM) analysis. The extracted α-chitin was then used as an adsorbent to remove synthetic dyes, namely Malachite green, Basic red 18, and Alizarin yellow R. The kinetic study showed that the adsorption of dyes was well-described using a pseudo-second-order model, whereas the isotherm adsorption obeyed the Freundlich model. The Frontier Molecular Orbital (FMO) revealed several locations of dyes and chitin molecules that are potentially active sites for adsorption. The adsorption trend could be related to the Highest Occupied Molecular Orbital (HOMO) – Lowest Unoccupied Molecular Orbital (LUMO) energy gap and electrophilicity index of the dyes. The Conductor-like Model for Real Solvent (COSMO-RS) model demonstrated, for the first time, that several interactions occurred during the adsorption of dyes onto α-chitin. For the Malachite green and Basic Red 18, the Van der Waals forces of the dyes controlled its adsorption behavior. In contrast, the hydrogen bonding interaction governed the adsorption behavior of Alizarin yellow R dye onto α-chitin. The gathered insight from this work might guide us better to understand the molecular level of dyes–chitin interactions and, ultimately, to design adsorbents to remove synthetic dyes from wastewater.